Supercomputing Frontiers 5th Asian Conference, SCFA 2019, Singapore, March 11-14, 2019, Proceedings - Abramson, David; de Supinski, Bronis R. (Theoretical Computer Science and General Issues,, 2019)
This open access book constitutes the refereed proceedings of the 5th Asian Supercomputing Conference, SCFA 2019, held in Singapore in March 2019. The 6 full papers presented in this book were carefully reviewed and selected from 33 submissions. They cover a range of topics including memory fault handling, linear algebra, image processing, heterogeneous computing, resource usage prediction, and data caching.